2018
DOI: 10.1590/1984-70332018v18n4a57
|View full text |Cite
|
Sign up to set email alerts
|

Diallel mixed-model analyses to select superior maize parental lines for Azospirillum brasilense and nitrogen-use efficiency

Abstract: Breeding new maize varieties that take up more N from the soil and increase N fixation is a crucial source of combined nitrogen in agricultural systems. Thus, this study aimed to select superior maize parental lines efficient in the use of nitrogen and Azospirillum brasilense. Three experiments were conducted in two agricultural seasons aiming to allocate all diallel hybrids in three different nitrogen conditions. The experiments were performed in a RCB design with two replications, and the diallel was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The experiment by Pereira & Tozoni (2017) indicates favorable results depending on the affinity of the cultivar with the microorganism strain. This corroborates Hungria (2011) and other authors who observed functional nitrogenase activity depending on the bacterial strain and the genetic material of maize (Brusamello-Santos et al, 2017;Pereira-Defilippi et al, 2017;Buzinaro et al, 2018;Revolti et al, 2018).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The experiment by Pereira & Tozoni (2017) indicates favorable results depending on the affinity of the cultivar with the microorganism strain. This corroborates Hungria (2011) and other authors who observed functional nitrogenase activity depending on the bacterial strain and the genetic material of maize (Brusamello-Santos et al, 2017;Pereira-Defilippi et al, 2017;Buzinaro et al, 2018;Revolti et al, 2018).…”
Section: Resultssupporting
confidence: 91%
“…In the experiment by Buzinaro et al (2018), the estimates for the effects of GCA for efficiency to Azospirillum in plant height, ear height, and grain yield, as well as for the effects of SCA for efficiency in grain yield, were significant. The authors concluded that additive effects influence the genetic control of the three traits in question, and that nonadditive effects influence the genetic control of the trait grain yield.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The mixed model methodology, or the residual maximum likelihood (REML)/best linear unbiased prediction (BLUP) [ 16 , 17 ] procedure, has been widely adopted for analyzing MET in plant breeding [ 18 21 ]. However, diallel analyses are still underused [ 22 ], even being an effective procedure for genetic evaluation [ 23 ].…”
Section: Introductionmentioning
confidence: 99%